Kepala Rumah Tangga Perempuan Pekerja Sektor Informal di Indonesia: Situasi dan Tantangan - Dodi Satriawan (Jurnal Wanita dan Keluarga, 2022)
The percentage of female-headed households tends to increase from year to year, where in 2012 the percentage of female-headed households reached 14.4%. This literature review aims to compare the characteristics of Male Heads of Households (MHH) and Female Heads of Households (FHH) working in the informal sector based on data from August 2017-2019. Based on the results of the study, it is known that from the total workers in the informal sector, characteristics are obtained that can distinguish between MHH and FHH. In MHH, it is dominated by workers with marital status, working in agricultural business fields, sufficient working hours (> = 35 hours), having low income, education after elementary school, being in a fairly young age group of 30-49 years. Meanwhile, FHH is dominated by workers with dead divorced marriage status, working in trading businesses, lacking working hours (<35 hours), having low incomes, education not graduating from elementary school, and being in the old age group of 50-64 years. Based on these characteristics, the government can provide guidance and provide facilities and capital assistance to informal sector workers, especially in MHH and FHH who are productive, work in the agricultural and trade sectors, have a low level of education, and those who work with high working hours in order to improve the standard of living of both mhh and fhh and their families. In addition, the attention from the government is expected to shift their status from those who initially worked in the informal sector slowly but surely to enter the formal sector.